THE CORRELATION BETWEEN STUDENTS' SELF-ESTEEM AND THEIR ENGLISH PROFICIENCY TEST RESULT - Septivana Gultom; Lulud Oktaviani (Journal of English Language Teaching and Learning, 2022)
Nowadays, a wide range of professions around the world employs English as an International Language. Many people learn English to keep up with the worldwide advances in areas like education, technology, tourism, health, and economics. English is widely utilized in many facets of human life. English is additionally necessary for graduation. Students must pass the English proficiency test to graduate from university (EPT). Self-esteem, an essential component of personality, affects people's attitudes and behaviors. Self-esteem is frequently associated with good mental health, effective living, successful learning, and even a good quality of life. How people view themselves, whether favorably or unfavorably, is a measure of their self-esteem. Since self-esteem and academic performance are intertwined, the researchers want to know whether or not students' self-esteem correlates with their level of English proficiency. This study, which involved 38 participants from Universitas Teknokrat Indonesia, used the quantitative method. This study's conclusions showed a connection between students' self-esteem and their EPT score. The researchers conclude that students' self-esteem did have an impact on their EPT score, i.e., the greater their self-esteem, the higher their EPT score.